Aplicaciones tecnológicas del molino coloidal en procesos de transformación agroindustrial - Duque Chiluisa, María Gabriela (2023)
This degree project is focused on making a complete operation and maintenance manual of a colloid mill specialized in different agro-industrial transformation processes, such as pasta. The equipment is located in the Fruit and Vegetable Research Laboratory, through which students will carry out pedagogical learning practices in order to develop and expand their theoretical and practical knowledge. The implementation of this project required different methods and types of research, which allowed a correct resolution and development of the manual, thus avoiding possible inconveniences during its execution and made it possible to achieve the established objectives, allowing the students to receive a manual with detailed technical information on the operation and preservation of the equipment, as well as basic safety principles for both the operator and the machinery. Therefore, in order to verify the operation of the equipment, peanut paste was used as a practical exercise. This demonstrative practice allowed to demonstrate the efficient operation of the equipment as well as its performance. In addition to providing detailed information on the assembly and mounting of the equipment.